Management of Jugular Bulb Injury During Transcanal Endoscopic Tympanoplasty. Issue 8 (September 2021) - Amorosa, Luca; Molinari, Giulia; Botti, Cecilia; Presutti, Livio
Abstract : N/A: Variable internal jugular vein anatomy is not rare. A high jugular bulb (JB) is reported in 6 to 34% of cases and, it can be jeopardized during middle ear surgery, especially if dehiscent. Its injury represents a threatening complication of ear surgery. In recent years there has been an increasing trend in the use of endoscopic ear surgery for a wide range of otologic procedures, but being a one-hand technique, the management of bleeding still represents a challenge. The aim of this video, http://links.lww.com/MAO/B280 is to report the endoscopic surgical management of internal jugular vein hemorrhage during endoscopic type I tympanoplasty. Abstract : Supplemental Digital Content is available in the text